Optimasi Penggunaan Kontainer dengan Algoritma Hill-Climbing - Heksa Bekti Ariyono; Bobi Hartanto (Universitas Bunda Mulia, 2017)
Problems that often happen is the charge that would like included in the container exceeds or is far less than the maximum volume of container space. In the case of the process of door to door or door to port, overloaded force clients should reduce the number of items that must be sent in order to fit with container capacity. While less than the maximum load that makes a lot of wasted container space volume that causes the client to fill it with stuff that does not exist in the delivery plan or let it remain fully charged with the costs of ineffective. The purpose of this field study is to maximize the use of volume of space in the container with the method of hill-climbing algorithm and utilize software programs created with Microsoft Visual Basic 6.0. Processing the data shows that during the delivery of goods, the utilization rate of container volume ranges from 44.185% to 72.630%. By using optimization calculation based on hill-climbing algorithm in the program made, the utilization rate of container volume can be optimized from the original 66.563% to 91.895% with an increase of 25.332%.Keywords: Supply Chain, Hill-Climbing Algorithm, Optimization